Descriptive Statistics For Demographic Tourist Visits On New Religious Segment: Evidence From TGKH. M. Zainuddin Abdul Madjid Tomb, Lombok Timur - Irwan Rahadi; Muhammad Ali Sukran; Muhammad Adi Junaidi; Hasan Basri; Muhammad Ramli; Zaitun Zaitun; Yogi Birrul Walid Sugandi (Enrichment : Journal of Management, 2022)
Tourist visits for religion in Indonesia already have their potent market. Tradition factors and religious diversity that thrive are why the potential religious segment is developed as a tourist attraction bringing economic benefits. This research then discussed the demography of visitors to the sacred tomb TGKH M. Zainuddin Abdul Madjid in Lombok Timur regency for four months, from March to June 2020. We employ the case study of research at the tomb of TGKH. M. Zainuddin Abdul Madjid, by only processing quantitative data, then described qualitatively. The data sources analysed were visitors from all West Nusa Tenggara province districts and outsiders. The findings concluded that tourists visiting the tomb of TGKH M. Zainuddin Abdul Madjid experienced a positive trend despite the decline at the end of the month due to PSBB (covid large-scale social restriction). Most visits came from the Lombok Timur regency, where Sikur, Selong, and Masbagik districts were the most significant attributes of visits. Central Lombok and West Lombok are in the second position with the dominant number of visits. The origin of the minor visit comes from outside West Nusa Tenggara, and North Lombok regency, where the Bayan district is the area visited the most during the data collected.